KETERLIBATAN PENTAHELIX DALAM PENGELOLAAN BANK SAMPAH - Muhammad Daffa Rizqi Eko Putra; Santoso Tri Raharjo (Social Welfare Study Program, 2023)
Abstract. A company's CSR program cannot be implemented alone, but requires the support of the involvement of various parties in order to achieve the expected goals. These various parties or stakeholders can consist of individuals, groups, or organizations as well as communities or governments; expected to contribute and be involved in the implementation of CSR programs. The involvement of various stakeholders is one of the key factors that need to be considered, considering the effectiveness and efficiency in achieving the program, as well as the sustainability of empowerment. There are at least 5 (five) categories of stakeholders who can be involved and collaborate in CSR programs, namely Academic, Business, Community, Government and Media (ABCGM). Each stakeholder plays a different role according to their respective capacities and abilities, as well as their respective authorities. The purpose of this research is to describe the involvement and collaboration of stakeholders in environmental management CSR programs, especially in the management of waste banks. A qualitative approach with a descriptive method is used to describe the involvement of stakeholders in the CSR program